Pengenalan Game Edukasi Android Sebagai Penunjang Perkembangan Kognitif Anak - Ela Suryani; Kartika Yuni Purwanti (Universitas Muhammadiyah Surabaya, 2019)
Community service activities performed in PKK Payungan Village, Kaliwungu District Semarang Regency help to parents understand educational games android decent child consumed. Educational games to support cognitive development of children so that parents must understand the various types of educational game applications, how to choose the right educational game, and how to install on the phone The implementation method used was presentation, demonstration, practice, brainstorming, and sharing about educational game to PKK Payungan Village. This activity is done through three stages: 1) socialization, 2) mentoring, 3) monitoring and evaluation.The results of the implementation of this activity was : 1) understanding educational games android as supporting the cognitive development of children in very good category. This is indicated by the percentage of achievement indicators of educational games (96%), choosing educational games (89%), installing educational games (93%), and implementing educational games (86%); 2) get positive response seen from indicator attendance reaches 93% of target and enthusiastic participant during activity from beginning to end of activity. The final goal of the introduction of educational games was IT literacy parent so as to be able to monitor their children in using mobile phones especially when playing games.